Validasi Metode Kromatografi Lapis Tipis untuk Penentuan Konsentrasi Kurkumin dalam Sampel Disolusi yang Mengandung Ektrak Curcuma longa - DEWI SETYANINGSIH; YOSI BAYU MURTI; ACHMAD FUDHOLI; WOUTER L.J. HINRICHS; ROCHMAT MUDJAHID; SUDIBYO MARTONO; TRIANA HERTIANI (Fakultas Farmasi Universitas Pancasila, 2016)
Curcumin is a lipophilic compound which suffers from the poor bioavailability after oral administration. Increasing its dissolution rate can be a successful strategy to improve the bioavailability. Along with the formulation developments, a rapid and simple analytical method to determine curcumin concentrations in the dissolution medium is required. The aim of this study was to develop and to validate an analytical method based on thin layer chromatography (TLC) to determine curcumin concentrations in a dissolution medium containing 0.5% w/v sodium lauryl sulfate (SLS) and 20 mM sodium phosphate buffer. A polyvinylpyrrolidone K30 based solid dispersion of Curcuma longa extract and its corresponding physical mixture were dissolved in a medium containing 0.5% w/v SLS and 20 mM sodium phosphate buffer (pH 6.0). Dissolution samples were spotted on a normal TLC plate and eluents of various compositions were evaluated. The retardation factor (Rf), resolution (Rs), and asymmetry factor (As0.05) of the optimized method were determined. Using the optimized eluent, proper separation of curcumin peak was achieved with an Rf of 0.50, Rs of 2.62 and As 0.05of 0.87. Linearity (5-30 μg/mL) was demonstrated by r value of 0.9965. The TLC method provided precision with RSD ≤3.50 and accuracy with recovery value of 94-105%.